2023
DOI: 10.3390/ma16175999
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Analysis of Calcium Carbonate Particle Trajectory Simulation in a Dual Horizontal Shaft Mixer

Guozheng Song,
Faguo Huang,
Jiafang Pan

Abstract: This article aims to investigate the feasibility of using discrete element software EDEM 2022.0 to simulate the trajectory of artificial marble patterns in a dual horizontal shaft mixer. Research was conducted on the mixing uniformity of particles in the mixing chamber, and the optimal speed range for particle mixing was established. By simulating the trajectory of pigment particles, the trajectories of the particles at different positions of the stirring paddle were obtained, and the trajectories were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…After the Chuanxiong-soil residue is thrown upwards, by integrating equation (20) with time t, the velocity of the Chuanxiong-soil residue relative to the x′-axis and y′-axis directions of the vibrating screen (v′x′ and v′y′) is obtained through Equation ( 21):…”
Section: Motion Analysis Of the Chuanxiong-soil Residue Thrown Upward...mentioning
confidence: 99%
See 1 more Smart Citation
“…After the Chuanxiong-soil residue is thrown upwards, by integrating equation (20) with time t, the velocity of the Chuanxiong-soil residue relative to the x′-axis and y′-axis directions of the vibrating screen (v′x′ and v′y′) is obtained through Equation ( 21):…”
Section: Motion Analysis Of the Chuanxiong-soil Residue Thrown Upward...mentioning
confidence: 99%
“…Ma et al [19] found that the rotation angle of the front swing bar has a positive influence on the backward movement rate of particles. Song et al [20] studied the motion trajectory to determine the optimal speed range for particle mixing and transportation. Yang et al [21] studied the forces, stratification mechanisms, and throwing principles of materials on the screen.…”
Section: Introductionmentioning
confidence: 99%
“…EDEM, notably the first modeling and simulation software developed using the DEM [16], has proven successful in various fields. Examples of its application include characterizing material movement in loader shovels [17], analyzing particle trajectories in mixers [18], and understanding the crushing process of gold-bearing ore in a jaw crusher [19]. The built-in JKR model [20] within EDEM is a cohesive contact model, taking into account the influence of van der Waals forces within the contact zone.…”
Section: Introductionmentioning
confidence: 99%